2020
DOI: 10.1108/ijdrbe-07-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gaps in early warning mechanisms and evacuation procedures for coastal communities in Sri Lanka

Abstract: Purpose Even though Sri Lanka has established Early Warning (EW) mechanisms and Evacuation Procedures (EP) for the communities affected by the coastal disasters, there are several gaps, which hinder effective mechanisms in operation of disaster management practices. These gaps affect both the vulnerable communities and relevant authorities involved in the Disaster Management sector. This paper aims to identify and evaluate those gaps while providing adequate solutions. Design/methodology/approach For that, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Currently, dedicated mobile applications and social media have become the most efficient and popular in terms of emergency response and disaster informationsharing platforms globally (Shehara et al, 2019a). However, a recent study carried out in the coastal areas of Sri Lanka has concluded that the use of modern communication channels for disaster communication is low at the village level for disaster communication (Perera et al, 2020).…”
Section: Modes Of Ew Dissemination and Use Of New Technologies For Disaster Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, dedicated mobile applications and social media have become the most efficient and popular in terms of emergency response and disaster informationsharing platforms globally (Shehara et al, 2019a). However, a recent study carried out in the coastal areas of Sri Lanka has concluded that the use of modern communication channels for disaster communication is low at the village level for disaster communication (Perera et al, 2020).…”
Section: Modes Of Ew Dissemination and Use Of New Technologies For Disaster Communicationmentioning
confidence: 99%
“…Lack of space, drinking water, and sanitary facilities have become a major issue, especially for people with special needs (Jayasiri et al, 2018b). Currently, the cooperation of local government and sub-national administrative officials in the country related to evacuation planning is not satisfactory (Perera et al, 2020). Lack of funding, lack of preparedness on evacuation plans, less information, and limited use of technology can be identified as major reasons behind these existing conditions (Malalgoda, 2014).…”
Section: Response Of Authoritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the most frequently used technologies for warning the public are sirens (Bubar et al, 2020;Kuligowski, Kuligowski, & Doermann, 2018;Perera et al, 2020;Piciullo, Calvello, & Cepeda, 2018) that are publicly announced, electronic media and the staff of competent institutions that go on the streets and inform the citizens by using appropriate speakers or megaphones (Sorensen, 2000). All the mentioned ways of informing the citizens have their advantages and disadvantages, as well as innovative improvements or alternative replacements.…”
Section: Introductionmentioning
confidence: 99%
“…Early warning systems designed for volcano, earthquake, tsunami, and ood risks may appear inadequate when dealing with illnesses like COVID-19 (Cvetković et al, 2020;Fearnley & Dixon, 2020;Öcal, Cvetković, Baytiyeh, Tedim, & Zečević, 2020). For these reasons, continuous improvement of early warning systems (LaBrecque, Rundle, & Bawden, 2019;Perera et al, 2020;Yang, Zhang, Wang, & Tang, 2018) is needed to respond to all the natural and anthropogenic risks faced by the community. In the future, cell phones might be used to communicate outlooks and warnings to rural locations that lack communications infrastructure, as could satellite-based broadcasts of danger warnings to remote areas (Glantz, 2003;Indrasari, Iswanto, & Andayani, 2018;Toya & Skidmore, 2018).…”
Section: Introductionmentioning
confidence: 99%